Relationship between seminal plasma trace elements and sperm quality - Yujie Li; Xiaowen Liu; Zewei Yu; Yangying Xu; Wei Xue; Xin Du; Guanghui Yuan; Xiaoxiao Wang; Yingxue Liu; Duan Li; Cuifang Hao (Ecotoxicology and Environmental Safety)
Male fertility has declined recently, mainly due to reduced sperm quality. While common factors contribute to this issue, they do not adequately explain all cases. Environmental pollutants, especially trace elements, significantly affect sperm quality, but the link between trace element exposure in seminal plasma and male fertility decline is still poorly understood. Here, inductively coupled plasma mass spectrometry was employed to detect 25 trace elements in seminal plasma from 209 Chinese men of reproductive age. The study utilized logistic regression and restricted cubic splines to examine the relationship between specific trace elements and semen parameters across different groups. Group comparisons revealed that the concentrations of Mg, Ca, Fe, Cu, Zn, Mn, Sr, Cd, and Co were significantly higher in patients with asthenozoospermia. The concentration of Mo was significantly lower in patients with teratozoospermia. Notably, the trace element exposure levels in patients with oligozoospermia were comparable to those of healthy individuals. Additionally, correlation analyses indicated that Mg, Ca, Fe, Zn, As, and Cd levels positively correlated with sperm DFI. Furthermore, significant positive correlations were identified between the Mg, Fe, Zn, and Tl concentrations and sperm concentration. Low Cu, Mn, and Co levels positively correlated with sperm concentration. Mg, Zn, Cd, and low concentrations of Co were negatively correlated with sperm motility. This study presents the largest-scale profile of trace element exposure in seminal plasma to date, emphasizing the significance of seminal trace elements as biomarkers that accurately reflect the environmental exposure levels of male germ cells. Our findings suggest that increased trace elements, particularly metal elements, in seminal plasma primarily reduce sperm motility rather than affecting sperm concentration or morphology. Further studies are needed to explore the biological mechanisms that link seminal trace elements to male fertility decline.